Banks’ efficiency and credit risk analysis using by-production approach: the case of Iranian banks - Salim, Ruhul; Arjomandi, A.; Dakpo, K. (Routledge, 2017)
This article uses a by-production approach that integrates credit risk to monitor bank efficiency. The method overcomes the possible misspecification issues of the commonly assumed weak disposability (WDA) of undesirable outputs. In addition, our measure extends the classic by-production approach by including statistical aspects through subsampling techniques. We have also provided an algorithm to correct related infeasibilities. Using this approach, we investigate the performance of Iranian banks and credit risk management in the sector for the period 1998–2012. Non-performing loans (NPLs) have been used as an undesirable output and proxy for credit risk in our models. Based on our empirical results, although the banks generally exhibited efficiency improvements over time, their credit risk performance deteriorated considerably after the regulatory changes introduced in 2005. These findings confirm that credit quality can be monitored more actively across Iranian banks.